Inquiry-based Ethnoecological Conservation Approach to Improve Students' Critical Thinking Skills - Ebikabowei Musah; Caroline Wangila (International Journal of Ethnoscience and Technology in Education, 2024)
This study explores the effectiveness of an inquiry-based ethnoecological conservation approach in enhancing critical thinking skills among students. Amidst growing concerns over environmental degradation, the integration of ethnoecological knowledge within educational frameworks emerges as a potent tool for fostering environmental stewardship and critical thinking. This research adopts a mixed methods design, engaging 45 secondary school students in a two-month pedagogical intervention that blends inquiry-based learning with ethnoecological insights. The intervention's impact on critical thinking was assessed using pretest-posttest analysis, supplemented by qualitative insights from student interviews. Quantitative results demonstrate a significant improvement in students' critical thinking skills post-intervention, with statistical analysis revealing a notable increase in mean scores and a reduction in score variability. This indicates not only an enhancement in critical thinking abilities but also a homogenization of skills across the participant group, underscoring the universal efficacy of the approach. Qualitative findings further enrich these results, with students reporting a deeper understanding of environmental issues, a stronger connection to cultural heritage, and a heightened sense of responsibility towards conservation efforts. The study highlights the transformative potential of integrating indigenous knowledge systems into environmental education, advocating for a pedagogical shift towards more inclusive, culturally relevant learning frameworks. By engaging students in a contextually rich exploration of ecological and cultural interconnections, the inquiry-based ethnoecological approach proves effective in cultivating critical thinking, thereby equipping students with the cognitive tools necessary to navigate and address complex environmental challenges. This research contributes to the evolving discourse on environmental education, offering valuable insights into the role of ethnoecology and inquiry-based learning in developing critical thinking skills and fostering a generation of informed and engaged environmental stewards.